The transmission of foreign shocks to South Eastern European economies: A Bayesian VAR approach - Petrevski, Goran; Exterkate, Peter; Tevdovski, Dragan; Bogoev, Jane (Elsevier BV, 2015)
The paper analyses the macroeconomic effects of foreign shocks in three South-East European (SEE) economies: Croatia, Macedonia and Bulgaria. In this regard, we investigate the transmission of several eurozone shocks (output gap, money market rates and inflation) on various macroeconomic variables in the aforementioned countries (output, inflation, money market rates and budget deficits). We trace the effects of foreign shocks on the basis of impulse response functions obtained from the Bayesian Vector Auto Regressions (VARs) separately for each country. The main findings from our study are: first, economic expansion in the eurozone has strong output and inflation effects on SEE economies, implying some degree of synchronization of business cycles; second, eurozone inflation is instantly and to a great extent transmitted to domestic inflation, suggesting that inflation in the SEE economies is mostly driven by foreign inflation; third, domestic money market rates are not closely linked with eurozone money markets; fourth, monetary policy in the SEE countries does not seem to be responsive to eurozone inflation shocks; and fifth, the fiscal authorities attempt to offset the spillover effects from both economic expansion and monetary tightening in the eurozone.
Keywords: Monetary policy; Bayesian Vector Autoregression; Exogenous shocks